Strategy for Developing Small-Scale Arabica Coffee Processing Industries in Gegerbitung District, Sukabumi Regency - Nidurama, Bayu Eka; Muhandri, Tjahja; Sudradjat, Sudradjat (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2026)
This study aims to formulate development strategies for small-scale coffee processing industries focusing on Arabica coffee in Gegerbitung District, Sukabumi Regency. Arabica coffee is a high-value commodity with growing global demand; however, local small industries still face challenges in processing technology, capital access, human resource capacity, and market linkage. A descriptive-analytical approach was employed using primary data obtained from field observations, interviews, and questionnaires involving 100 respondents (farmers and small coffee processors) and nine experts from relevant institutions, supported by secondary data from official publications and literature. Strategic formulation was conducted through the stages of Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT, Internal-External (IE) matrix, and Quantitative Strategic Planning Matrix (QSPM). The results show IFE and EFE scores of 2.78 and 2.72, respectively, placing the industry in the “Hold and Maintain” position. Eight key strategies were identified, with the highest Total Attractiveness Score (TAS) of 7.15 assigned to improving human resource capacity through integrated training programs. This strategy serves as a foundation for implementing digital marketing, product innovation, and geographical indication-based branding to enhance competitiveness and ensure the sustainability of Arabica coffee small industries at the local level